The dynamics of light-induced interfacial charge transfer of different dyes in dye-sensitized solar cells studied by ab initio molecular dynamics. Issue 48 (12th October 2021) - He, Lanlan; Guo, Yu; Kloo, Lars
Abstract : The charge-transport dynamics at the dye–TiO2 interface plays a vital role for the resulting power conversion efficiency (PCE) of dye sensitized solar cells (DSSCs). Abstract : The charge-transport dynamics at the dye–TiO2 interface plays a vital role for the resulting power conversion efficiency (PCE) of dye sensitized solar cells (DSSCs). In this work, we have investigated the charge-exchange dynamics for a series of organic dyes, of different complexity, and a small model of the semiconductor substrate TiO2 . The dyes studied involve L1, D35 and LEG4, all well-known organic dyes commonly used in DSSCs. The computational studies have been based on ab initio molecular dynamics (aiMD) simulations, from which structural snapshots have been collected. Estimates of the charge-transfer rate constants of the central exchange processes in the systems have been computed. All dyes show similar properties, and differences are mainly of quantitative character. The processes studied were the electron injection from the photoexcited dye, the hole transfer from TiO2 to the dye and the recombination loss from TiO2 to the dye. It is notable that the electronic coupling/transfer rates differ significantly between the snapshot configurations harvested from the aiMD simulations. The differences are significant and indicate that a single geometrically optimized conformation normally obtained from static quantum-chemistry calculations may provide arbitrary results. Both protonated and deprotonated dye systems were studied. The differences mainly appear in the rate constant of recombination loss between the protonated and the deprotonated dyes, where recombination losses take place at significantly higher rates. The inclusion of lithium ions close to the deprotonated dye carboxylate anchoring group mitigates recombination in a similar way as when protons are retained at the carboxylate group. This may give insight into the performance-enchancing effects of added salts of polarizing cations to the DSSC electrolyte. In addition, solvent effects can retard charge recombination by about two orders of magnitude, which demonstrates that the presence of a solvent will increase the lifetime of injected electrons and thus contribute to a higher PCE of DSSCs. It is also notable that no simple correlation can be identified between high/low transfer rate constants and specific structural arrangements in terms of atom–atom distances, angles or dihedral arrangements of dye sub-units.